Fine Needle Aspiration Cytology for Early Detection of Cutaneous Metastases: Insights from a Tertiary Care Center - Madhumita Mukhopadhyay; Ananya Ghatak; Chhanda Das; Subhamoy Saha; Binata Bandopadhyay; Malabika Baisya; Rituparna Kayal; Biswanath Mukhopadhyay (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
Introduction: Skin metastasis can be the presenting symptom of many malignant tumors. These signs occur a long time before the diagnosis of the primary tumors or their recurrence and sometimes after surgery. These initial cutaneous tumors may aid in the diagnosis of primary tumors. Aim: This study was conducted to identify them and to establish the utility of Fine Needle Aspiration Cytology (FNAC) to diagnose these lesions. As FNAC is a simple, rapid, cost-effective, minimally invasive OPD procedure. No anesthesia or special equipment is needed and it can be practised in a small setup. Materials and Methods: The study was conducted in a tertiary care center. Clinical history, presenting features, and FNAC findings of the cutaneous lesions were noted. Immunocytochemistry(ICC) and Immunohistochemistry (IHC) from cell block were done when necessary. These findings then corroborated with Histopathological diagnosis. Results: This study includes the cases of cutaneous metastatic deposits from various primary visceral malignancies, Lung, Gastrointestinal tract, thyroid, ovary etc. at different sites. The sites of cutaneous metastasis are the chest wall, scalp, and anterior abdominal wall, all over the body. The patients underwent preliminary investigations and FNAC. After a diagnosis of neoplastic lesions, the patients were referred to the Radiology, surgery, and radiotherapy department for further management. Conclusion: Metastatic skin lesions may develop due to lymphatic and blood spread. It may be the first presenting feature of the malignant tumor or its recurrence. This study also proves the efficacy of FNAC in ascertaining the nature of these lesions. The cytological features along with clinical findings and radiological imaging help the early recognition of the primary lesion or identification of recurrence and thus help the clinicians in planning appropriate management.